2019
DOI: 10.1007/s12020-019-01918-9
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical carcinoma: presentation and outcome of a contemporary patient series

Abstract: Background Adrenocortical carcinoma (ACC) is a rare endocrine carcinoma with poor 5-year survival rates of < 40%. According to the literature, ACC is rarely an incidental imaging finding. However, presentation, treatment and outcome may differ in modern series. Design and methods We studied all patients ( n = 47, four children) from a single centre during years 2002–2018. We re-evaluated radiologic and histopathological findings and assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 43 publications
3
38
0
6
Order By: Relevance
“…Our study shows that less than a quarter of patients were alive after 3 years of follow-up, with a median survival of 35 months. These data confirm the high mortality of advanced ACC [12,14]; however, they also follow the trend of a better prognosis observed in the most recent studies [13]. The present study shows that the lung is the organ most commonly involved by metastatic spread, with a higher frequency than previously reported in clinical series [14] but with a similar rate of autoptic [15] or surgical series [16,17].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study shows that less than a quarter of patients were alive after 3 years of follow-up, with a median survival of 35 months. These data confirm the high mortality of advanced ACC [12,14]; however, they also follow the trend of a better prognosis observed in the most recent studies [13]. The present study shows that the lung is the organ most commonly involved by metastatic spread, with a higher frequency than previously reported in clinical series [14] but with a similar rate of autoptic [15] or surgical series [16,17].…”
Section: Discussionsupporting
confidence: 92%
“…In the overall group, the achievement of target mitotane levels required a median time of 6 (3-9) months from the start of therapy while 14 patients (17.5%) never achieved levels ≥ 14 mg/L. The peak of plasma mitotane concentrations was 20.8 (14.8-25.0) mg/L, which was reached after a median of 11 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recently published guidelines on the management of ACC suggest that laparoscopic adrenalectomy is acceptable in tumours smaller than 6 cm 6 . However, several studies demonstrated that in specialized referral centres laparoscopic surgery for ACC represents the appropriate surgical approach in patients with a tumour diameter of up to 10 cm if the principles of oncologic surgery are respected 10,16 . In support of these data, in the present study, the majority of patients in the LA group (57%) had a tumour larger than 6 cm (7‐11 cm) and only one of them experienced tumour recurrence, 28 months after the laparoscopic surgery.…”
Section: Discussionsupporting
confidence: 81%
“…showed that laparoscopic adrenalectomy was successful for the selected cases with tumor size ranging from 6 to 10 cm without local invasion and resulted in shorter hospitalization and showed comparable survival rate with open adrenalectomy. [ 8 ] Our patient demonstrated that laparoscopic adrenalectomy can be safely applied to bilateral ACC with tumor size exceed to 12.5 cm. However, the 1 cm metastatic paraaortic lymph node that noted on PET/CT images could not be depicted intraoperatively due to its small size.…”
Section: Discussionmentioning
confidence: 86%